(NfOTOGRAMMETRIQ (B:s [(Nu^EB(B. (NDLQ WUZOW PO SPEC(B. "(NmARK[EJDER(B. (NDELO(B" /s - (NkELLX(B, (Nl(B. (Nn(B. s; (N~ERKASOW(B, (Ni(B. (Na(B.s; (NpONOMAREW(B, (Ne(B.(Nw(B.s; (NkORNILOW(B, (N`(B.(Nn(B.s ((NmOSKWA (B:s (NnEDRA(B,s, 1989)
(NbIBLIOGR(B.: (NS(B. 312 (17 (NNAZW(B.)s
(NpREDM(B. (NUKAZ(B.: (NS(B. 313-316s
(NaWT(B. (NUKAZANY NA OBOROTE TIT(B. (NL(B.s
Keywords: (NfOTOGRAMMETRIQs; (NfOTOGRAMMETRIQ (B- (NpRIMENENIE W GORNOM DELE (B- (Nu^EBNIKI I POSOBIQs